Magnetic Resonance Imaging of Bioresorbable Vascular Scaffolds. (April 2015) - Reiss, Simon; Krafft, Axel J.; Zehender, Manfred; Heidt, Timo; Pfannebecker, Thomas; Bode, Christoph; Bock, Michael; von zur Muhlen, Constantin
<x xml:space="preserve">Abstract</x> Supplemental Digital Content is available in the text.